Tuberculosis Outbreak Investigations in the United States, 2002–2008 - Kiren Mitruka; John E. Oeltmann; Kashef Ijaz; Maryam B. Haddad (2011)
Abstract To understand circumstances of tuberculosis transmission that strain public health resources, we systematically reviewed Centers for Disease Control and Prevention (CDC) staff reports of US outbreaks in which CDC participated during 2002–2008 that involved >3 culture-confirmed tuberculosis cases linked by genotype and epidemiology. Twenty-seven outbreaks, representing 398 patients, were reviewed. Twenty-four of the 27 outbreaks involved primarily US-born patients; substance abuse was another predominant feature of outbreaks. Prolonged infectiousness because of provider- and patient-related factors was common. In 17 outbreaks, a drug house was a notable contributing factor. The most frequently documented intervention to control the outbreak was prioritizing contacts according to risk for infection and disease progression to ensure that the highest risk contacts were completely evaluated. US-born persons with reported substance abuse most strongly characterized the tuberculosis outbreaks in this review. Substance abuse remains one of the greatest challenges to controlling tuberculosis transmission in the United States.